Waugh's Syndrome: Report of Two Children with Intussusception - Khan, Yousuf Aziz; Yadav, Sunil Kumar; Elkholy, Ashraf (European Journal of Pediatric Surgery Reports, 2017)
Waugh's syndrome (WS) is the rare association of intussusception and intestinal malrotation. We present two such cases in a 5-month-old infant and a 9-year-old girl. Both patients presented with intussusception and were diagnosed with malrotation during workup and surgical exploration. We conclude that the possibility of intestinal malrotation must be taken into consideration while managing children with intussusception.
Keywords: Waugh's syndrome; intussusception; intestinal malrotation; children